Monstruosidades contemporâneas em Castle Rock: audiovisualidades monstruosas nas plataformas e mídias sociais - Silva, Flóra Simon da (Universidade do Vale do Rio dos Sinos, 2024)
This thesis investigates how technocultural movements between platforms, social media, and users update audiovisual monstrosities in their materialities, using the series Castle Rock by Stephen King and J.J. Abrams as the research corpus. The initial analysis of the series reveals that its monstrosities are updated in other digital materialities, transcending the boundaries of the original narrative. Therefore, the research aims to understand communicational phenomena, highlighting the importance of examining the particularities that reveal macro aspects of these phenomena. It proposes an analysis that goes beyond the specificity of the audiovisual product to understand broader media processes, connecting micro and macro phenomena in the collective social construction through techniques and aesthetics that manifest and perpetuate in different formats and devices, relating concepts of memory, user actions, and technical images. By observing how the monstrosities present in the series' narrative spread to other digital spaces, we use Didi-Huberman's (1998) concept of the dialectics of the image to understand how these audiovisual monstrosities manifest in communications via platforms and social media, forming what we call "monstrous audiovisualities." To identify the research corpus, we employed a methodological approach that involves flânerie and cartography. Flânerie, inspired by Benjamin (2009) and applied in the digital context, allowed us to explore streaming platforms like a flâneur, observing and being affected by the various representations of monsters in films and series. Based on these initial methodological movements and the choice of the corpus, the research ventured into other digital spaces, following the collections of monstrous meanings from the series, focusing on platforms and social media where we found dialectical monstrous aspects related to the series, according to the frame methodology (KILPP, 2002), considering its techno-aesthetic, social, and political implications within contemporary technoculture. The investigation revealed that digital platforms and social media are spaces where these monstrosities are updated, reflecting social and political aspects of our era's technoculture. By exploring virtual windows, the research highlighted how monsters manifest through platforms and user actions, demonstrating dialectical meanings with the audiovisual monstrosities of the Castle Rock series.
Keywords: Monstruosidades; Tecnocultura; Plataformas; Castle Rock; Stephen King; Monstrosities; Technoculture; Platforms; ACCNPQ::Ciências Sociais Aplicadas::Comunicação